Binder for non-aqueous secondary battery, slurry for porous layer of lithium ion secondary battery, porous layer of lithium ion secondary battery, separator for lithium ion secondary battery, and lithium ion secondary battery

A binder with a specific acrylamide and methacrylamide monomer ratio in a particulate copolymer addresses the issue of separator shrinkage at high temperatures, enhancing adhesion and heat resistance to improve lithium ion battery safety and performance.

JP7599233B2Active Publication Date: 2024-12-13ASAHI KASEI KOGYO KABUSHIKI KAISHA +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023099368
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-16
Publication Date
2024-12-13
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

Existing lithium ion secondary battery separators face challenges in suppressing shrinkage at high temperatures, leading to potential short circuits and safety issues, as current binder compositions do not provide sufficient heat resistance and adhesion at temperatures above 150°C.

Method used

A binder for non-aqueous secondary batteries comprising a particulate copolymer with a specific ratio of acrylamide and methacrylamide monomer units, which forms a layer that effectively suppresses separator shrinkage even at high temperatures through enhanced adhesion and heat resistance.

Benefits of technology

The binder composition ensures high adhesion and heat resistance, preventing separator shrinkage and short circuits at high temperatures, thereby improving the safety and performance of lithium ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599233000001
    Figure 0007599233000001
  • Figure 0007599233000002
    Figure 0007599233000002
  • Figure 0007599233000003
    Figure 0007599233000003
Patent Text Reader

Abstract

To provide a binder for a nonaqueous secondary battery, which enables the formation of a layer capable of suppressing separator shrinkage even under a high-temperature condition.SOLUTION: A binder for a nonaqueous secondary battery comprises: an aqueous medium; and a particulate copolymer. The particulate copolymer contains a vinyl monomer unit. The vinyl monomer unit contains an acrylamide monomer unit (B1) and a methacrylamide monomer unit (B2). A content W1(pts.mass) of the acrylamide monomer unit (B1) and a content W2 (pts.mass) of the methacrylamide monomer unit (B2) to a total mass, 100 pts.mass of the vinyl monomer unit satisfy the following requirement (1): 0<W1 / W2<1 (1), and the content W2 of the methacrylamide monomer unit (B2) is equal to or larger than 2 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder for a non-aqueous secondary battery, a slurry for a porous layer of a lithium ion secondary battery, a porous layer for a lithium ion secondary battery, a separator for a lithium ion secondary battery, and a lithium ion secondary battery. [Background technology]

[0002] 2. Description of the Related Art Conventionally, there has been active development of electricity storage devices, typified by lithium ion secondary batteries. In general, the lithium ion secondary battery has a separator made of a microporous membrane between the positive and negative electrodes, which prevents direct contact between the positive and negative electrodes and allows the electrolyte held in the micropores to pass through and allows ions to pass through. In recent years, in order to impart various properties to the separator while ensuring the electrical properties and safety of lithium-ion secondary batteries, a separator has been proposed in which a layer containing an inorganic filler and a resin binder is disposed on the surface of a substrate constituting the separator (see, for example, Patent Document 1). Patent Document 1 discloses a technology relating to a lithium ion secondary battery in which a resin composition containing polymer particles formed from a first monomer having an acidic functional group, a second monomer having an amide group, and another third monomer, and an inorganic filler is applied onto a separator, and a protective layer made of the resin composition is formed on the separator.

[0003] In lithium ion secondary batteries, an adhesive layer or the like may be provided on the surface of an electrode and / or a separator in order to improve adhesion between battery components. For example, an electrode with an adhesive layer formed on an electrode and a separator with an adhesive layer formed on a separator are used as battery components. Specifically, a technique has been disclosed in which a porous film containing polymer particles and inorganic filler is provided on a separator, and then an adhesive layer is provided between the separator and the electrode (for example, see Patent Document 2).

[0004] In recent years, there has been a demand for secondary batteries with even higher performance. One of the performances is to further ensure safety when the secondary battery is used in a high-temperature environment. As a technology for ensuring the safety of the secondary battery when used in such a high-temperature environment, for example, a non-aqueous secondary battery functional layer composition containing organic particles and a solvent has been proposed, and a technology has been disclosed in which the non-aqueous secondary battery functional layer composition is used as a material for forming a functional layer on a separator (see, for example, Patent Document 3). The functional layer in Patent Document 3 has high heat shrinkage resistance, and is said to be able to sufficiently suppress the occurrence of a short circuit between the positive electrode and the negative electrode in a high-temperature environment, thereby ensuring safety.

[0005] In a secondary battery, the micropores in the separator have a function of shrinking when the battery generates heat, thereby hindering the passage of, for example, lithium ions, and suppressing runaway of the secondary battery. However, there is a problem that when a secondary battery goes out of control at high temperatures of about 150° C. or higher, the separator shrinks and the electrodes short-circuit. In particular, as the capacity of batteries has increased in recent years, the amount of heat generated during runaway tends to increase, so there is a demand for technology to prevent separator shrinkage at high temperatures.

[0006] The non-aqueous secondary battery functional layer composition disclosed in Patent Document 3 contains organic particles and a solvent, and further contains an optional binder and other components. The organic particles contain a predetermined ratio of polyfunctional ethylenically unsaturated monomer units, and have a volume average particle size within a predetermined range. In addition, it is disclosed that the optional binder is a polymer containing a crosslinkable monomer unit such as allyl glycidyl ether and a repeating unit other than the crosslinkable monomer unit. The functional layer formed on the separator disclosed in Patent Document 3 is said to have high resistance to heat shrinkage and to ensure the safety of the secondary battery. However, there is still a problem in that there is room for improvement in suppressing the shrinkage of the separator at high temperatures of 150°C or higher.

[0007] Also, Patent Document 4 discloses a material for a functional layer containing a predetermined amount of an epoxy group-containing monomer. It is said that a functional layer formed from the material for a functional layer disclosed in Patent Document 4 has excellent flexibility in a low temperature range (e.g., 60°C) before the onset of thermal shrinkage, and becomes hard at high temperatures of 150°C or higher as thermal crosslinking progresses, has high heat shrinkage resistance, and can ensure the safety of a secondary battery. However, the material for the functional layer disclosed in Patent Document 4 has a low initial storage modulus, and therefore the storage modulus after thermal crosslinking at high temperatures of 150°C or higher is not sufficiently high. Therefore, there is still room for improvement in the effect of suppressing the shrinkage of the separator at high temperatures of 150°C or higher.

[0008] Furthermore, Patent Document 5 discloses a binder composition for an electricity storage device, and the binder composition for an electricity storage device is mainly composed of a water-soluble polymer in which the ratio of repeating units derived from (meth)acrylamide is 40 to 100% by mass. Although such a water-soluble polymer has excellent adhesion to inorganic pigments, when the binder composition for an electricity storage device is applied to a separator together with an aqueous medium, the polymer dissolved in the aqueous medium penetrates into the pores, causing clogging and tending to reduce the battery performance. In addition, the water-soluble polymer increases the water content of the separator, which increases the amount of water inside the battery and is likely to cause a side reaction in the electrolyte and cause early deterioration of the battery performance, and there is a problem in that there is room for improvement in this respect as well.

[0009] Furthermore, Patent Document 6 discloses a binder dispersion for non-aqueous secondary battery separators containing a particulate polymer containing 40 to 80 mass % of (meth)acrylamide. The binder dispersion for non-aqueous secondary battery separators contains a particulate copolymer obtained by copolymerization of an ethylene unsaturated monomer having a predetermined octanol / water distribution coefficient and the (meth)acrylamide. If the binder dispersion for non-aqueous secondary battery separators has such a form, it is considered that when it is applied onto a separator, it will increase the heat resistance of the separator while not impairing the conductivity. However, judging from the high water solubility of (meth)acrylamide and the viscosity of the binder dispersion, it contains a large amount of water-soluble polymer, and like the binder composition for electric storage devices disclosed in Patent Document 5, there is a problem that the particulate polymer dissolved in the aqueous medium penetrates into the inside of the pores, causing clogging and tending to reduce the battery performance.

[0010] Furthermore, Patent Documents 7 and 8 disclose binder compositions for non-aqueous secondary batteries that contain a copolymer polymer obtained by copolymerizing a (meth)acrylamide monomer and a (meth)acrylic acid ester monomer. Patent Documents 7 and 8 disclose that the binder compositions for non-aqueous secondary batteries have a high effect of improving adhesion to electrodes and / or separators. However, the high-temperature strength of the binder compositions for non-aqueous secondary batteries disclosed in Patent Documents 7 and 8 is not high enough, and there is a problem that there is room for improvement in suppressing the shrinkage of the separator at high temperatures of 150°C or higher. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Patent No. 5708872 [Patent Document 3] International Publication No. 2019 / 065416 Brochure [Patent Document 4] International Publication No. 2021 / 141119 Brochure [Patent Document 5] JP 2015-118908 A [Patent Document 6] Patent No. 7004104 [Patent Document 7] JP 2015-088484 A [Patent Document 8] JP 2015-185530 A Summary of the Invention [Problem to be solved by the invention]

[0012] As described above, the conventional techniques have a problem in that they have not yet been sufficiently effective in suppressing separator shrinkage at high temperatures of 150° C. or higher.

[0013] Therefore, an object of the present invention is to provide a binder for a non-aqueous secondary battery, which is capable of forming a layer that can suppress separator shrinkage even at high temperatures, for example, of about 150° C. or higher; a slurry for a lithium-ion secondary battery porous layer that contains the binder for a non-aqueous secondary battery; a lithium-ion secondary battery porous layer that contains the slurry for a lithium-ion secondary battery porous layer; a lithium-ion secondary battery separator that contains the lithium-ion secondary battery porous layer; and a lithium-ion secondary battery. [Means for solving the problem]

[0014] As a result of intensive research by the present inventors to achieve the above-mentioned object, they have found that, in a binder for non-aqueous secondary batteries containing a particulate copolymer containing vinyl monomer units, the vinyl monomer units contain acrylamide monomer units (B1) and methacrylamide monomer units (B2), and the content W1 (parts by mass) of the acrylamide monomer units (B1) and the content W2 (parts by mass) of the methacrylamide monomer units (B2) per 100 parts by mass of the total mass of the vinyl monomer units have a predetermined relationship, and the content W2 of the methacrylamide monomer units (B2) is a predetermined numerical value or more, by using such a binder for non-aqueous secondary batteries, separator shrinkage can be suppressed even at high temperatures, and have completed the present invention. That is, the present invention is as follows.

[0015] [1] A non-aqueous secondary battery binder comprising an aqueous medium and a particulate copolymer, The particulate copolymer contains vinyl monomer units, the vinyl monomer units include acrylamide monomer units (B1) and methacrylamide monomer units (B2); a content W1 (parts by mass) of the acrylamide monomer unit (B1) and a content W2 (parts by mass) of the methacrylamide monomer unit (B2) relative to 100 parts by mass of the total mass of the vinyl monomer units satisfy the following formula (1), The content W2 of the methacrylamide monomer unit (B2) is 2 parts by mass or more. the law of nature, The binder for a non-aqueous secondary battery is a binder for a functional layer included in a separator for a lithium ion secondary battery in the non-aqueous secondary battery. A binder for non-aqueous secondary batteries. 0 <W1 / W2<1 ···(1) [2] The binder for a non-aqueous secondary battery according to [1] above, wherein the particulate copolymer has a glass transition temperature of 10° C. or lower. [3] The binder for a non-aqueous secondary battery according to [1] or [2], wherein the particulate copolymer contains a vinyl monomer unit and a monomer unit derived from a reactive surfactant having a functional group copolymerizable with a vinyl group. [4] The vinyl monomer unit includes a crosslinkable monomer unit containing two or more vinyl groups, The content of the crosslinkable monomer unit containing two or more vinyl groups is 0.1 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the particulate copolymer. The binder for a non-aqueous secondary battery according to any one of [1] to [3] above. [5] The binder for a nonaqueous secondary battery according to any one of [1] to [4], wherein a content W2 of the methacrylamide monomer unit (B2) relative to 100 parts by mass of a total mass of the vinyl monomer units is 2 parts by mass or more and less than 20 parts by mass. [6] The particulate copolymer has a volume average particle diameter Dv and a number average particle diameter Dn, the ratio Dv / Dn being: The binder for a nonaqueous secondary battery according to any one of [1] to [5] above, wherein the molecular weight ratio is 1 or more and 1.5 or less. [7] The particulate copolymer is Storage modulus at 30°C is 7×10 7 Pa or more 5×10 8 Pa or less, Storage modulus at 130℃ is 2×10 6 Pa or more, The binder for a non-aqueous secondary battery according to any one of [1] to [6] above. [8] The binder for a non-aqueous secondary battery according to any one of [1] to [7], wherein the vinyl monomer unit further contains an epoxy group-containing vinyl monomer unit. [9] The binder for a non-aqueous secondary battery according to any one of [1] to [8], which is a binder for a porous layer in a non-aqueous secondary battery.

[10] Water, An inorganic filler; The non-aqueous secondary battery binder according to any one of [1] to [9] above, , including, Slurry for porous layers of lithium-ion secondary batteries.

[11] The slurry for a lithium ion secondary battery porous layer according to

[10] above is included. Lithium-ion secondary battery porous layer.

[12] The lithium ion secondary battery porous layer according to

[11] above is included. Separator for lithium-ion secondary batteries.

[13] A lithium ion secondary battery comprising the separator for lithium ion secondary batteries according to

[12] . Effect of the Invention

[0016] According to the present invention, a non-aqueous binder for secondary batteries is obtained that is capable of forming a layer that can suppress separator shrinkage even at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The following describes in detail an embodiment of the present invention (hereinafter referred to as the "present embodiment"); however, the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0018] In this specification, when the term "monomer" is used, this "monomer" includes all of the monomers constituting the particulate copolymer of this embodiment. In this specification, when a monomer is incorporated into a polymer, it is referred to as a "monomer unit", and the state before being incorporated into a polymer is referred to as a "monomer" or "compound".

[0019] In this specification, the term "(meth)acrylic acid ester" refers to both methacrylic acid ester and acrylic acid ester, and the term "(meth)acrylamide" refers to both methacrylamide and acrylamide.

[0020] [Binder for non-aqueous secondary batteries] The binder for a non-aqueous secondary battery of the present embodiment contains an aqueous medium and a particulate copolymer. The particulate copolymer contains vinyl monomer units, and the vinyl monomer units contain acrylamide monomer units (B1) and methacrylamide monomer units (B2). a content W1 (parts by mass) of the acrylamide monomer unit (B1) and a content W2 (parts by mass) of the methacrylamide monomer unit (B2) relative to 100 parts by mass of the total mass of the vinyl monomer units satisfy the following formula (1), The content W2 of the methacrylamide monomer unit (B2) is 2 parts by mass or more. 0 <W1 / W2<1 ···(1) According to the binder for a nonaqueous secondary battery of this embodiment, it is possible to form a porous layer that can effectively suppress separator shrinkage even at high temperatures of, for example, about 150° C. or higher.

[0021] Usually, a microporous separator for a secondary battery is provided with a layer for the purpose of imparting functions such as suppressing the thermal shrinkage of the separator. Examples of methods for forming the layer include a method of coating a composition containing an inorganic pigment, a latex, a dispersant, a thickener, etc., and an aqueous medium. In this case, the separator and the layer (also called a coating layer) are required to have high adhesion so as not to be peeled off. The present inventors conducted a study under the assumption that by increasing the adhesion, the coating layer would strongly support the separator and the thermal shrinkage of the separator would be effectively suppressed. However, as a result of the study, it became clear that a coating layer adjusted to have high adhesive strength simply for the purpose of increasing the peel strength could not sufficiently suppress the thermal shrinkage of the separator. Furthermore, as a result of the inventors' investigations, it was found that in addition to adhesion at room temperature, it is also important for the separator to exhibit high adhesion even at high temperatures, such as 150°C, at which the polyolefin-based base material constituting the separator begins to shrink. Furthermore, the inventors have found that when the coating layer contains a particulate copolymer containing a predetermined amount of an amide group-containing vinyl monomer, particularly a (meth)acrylamide monomer unit, as a polar component, the coating layer exhibits the desired behavior at low and high temperatures, and can effectively suppress thermal shrinkage of the separator even at high temperatures such as 150°C. Furthermore, the present inventors have found that in order to effectively introduce amide groups into the particulate copolymer, it is important to adjust the monomer distribution ratio between the aqueous medium and the particulate copolymer, specifically, to adjust the distribution ratio of the acrylamide monomer to the aqueous medium / particulate copolymer, and to mainly use methacrylamide monomer from the viewpoint of copolymerizability between the monomers, specifically, to compare the copolymerizability of the acrylamide monomer with other vinyl monomers and the copolymerizability of the methacrylamide monomer with other vinyl monomers, and to mainly use methacrylamide monomer, in view of the fact that methacrylamide monomer has higher copolymerizability and is more easily incorporated into the skeleton of the particulate copolymer.

[0022] (aqueous medium) The binder for a nonaqueous secondary battery of the present embodiment contains an aqueous medium. Examples of the aqueous medium include water, methanol, ethanol, isopropyl alcohol, and other solvents. The aqueous medium may contain a dispersant, a lubricant, a thickener, a bactericide, and the like.

[0023] (Particulate copolymer) The binder for a nonaqueous secondary battery of the present embodiment contains a particulate copolymer. The particulate copolymer contains vinyl monomer units.

[0024] <Vinyl monomer unit> The vinyl compound, which is a raw material monomer for forming the vinyl monomer unit that constitutes the particulate copolymer, is a monomer having a vinyl group, and the vinyl compound (CH 2 =CHX) and vinylidene compounds (CH 2Examples of the monomer include (meth)acrylic acid esters, (meth)acrylic acid, (meth)acrylamide, aromatic vinyl compounds, acrylonitrile, etc. Specific examples are described in detail below. These may be used alone or in combination of two or more.

[0025] <Monomer unit derived from a reactive surfactant having a functional group copolymerizable with a vinyl group> The particulate copolymer preferably contains the vinyl monomer unit and a monomer unit derived from a "reactive surfactant having a functional group copolymerizable with a vinyl group". The raw material monomer for forming a monomer unit having a functional group copolymerizable with the vinyl group, i.e., the reactive surfactant, may be a compound having a vinyl group, an acrylic group, or a methacrylic group, and specifically, may be a compound usable as a reactive surfactant as described below. These may be used alone or in combination of two or more.

[0026] The particulate copolymer using the vinyl monomer unit and the "monomer unit derived from a reactive surfactant having a functional group copolymerizable with a vinyl group" has excellent chemical stability, and the chemical structure of a separator using the binder for a nonaqueous secondary battery of this embodiment tends to be less decomposed even when exposed to oxidizing conditions, reducing conditions, and high-temperature conditions (e.g., 150°C) inside the battery.

[0027] <Methacrylamide monomer units in particulate copolymer> As described above, the particulate copolymer contains vinyl monomer units, and the vinyl monomer units contain an acrylamide monomer (B1) and a methacrylamide monomer unit (B2). The content W2 of the methacrylamide monomer unit (B2) contained in the particulate copolymer is 2 parts by mass or more, preferably 4 parts by mass or more, more preferably 6 parts by mass or more, and even more preferably 10 parts by mass or more, per 100 parts by mass of the total mass of the vinyl monomer units in the particulate copolymer. The upper limit of the content of methacrylamide monomer units (B2) is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, even more preferably less than 20 parts by mass, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of the total mass of vinyl monomer units in the particulate copolymer. By making the content of the methacrylamide monomer unit (B2) contained in the particulate copolymer 2 parts by mass or more per 100 parts by mass of the total mass of the vinyl monomer units in the particulate copolymer, the binder for nonaqueous secondary batteries of this embodiment has improved adhesion at room temperature and has an increased storage modulus at high temperatures (e.g., 130°C), and tends to be able to suppress the thermal shrinkage of the separator using the binder for nonaqueous secondary batteries of this embodiment. In addition, by making the content of the methacrylamide monomer unit (B2) 30 parts by mass or less per 100 parts by mass of the total mass of the vinyl monomer units in the particulate copolymer, the proportion of water-soluble components contained in the binder for nonaqueous secondary batteries of this embodiment is suppressed, and when the binder is applied as a slurry, clogging of the pores of the separator is reduced, and therefore battery characteristics such as cycle characteristics and rate characteristics tend to be improved.

[0028] As described above, the particulate copolymer contains acrylamide monomer units (B1) and methacrylamide monomer units (B2). The content W1 (parts by mass) of the acrylamide monomer unit (B1) and the content W2 (parts by mass) of the methacrylamide monomer unit (B2) relative to 100 parts by mass of the total mass of the vinyl monomer units have the relationship represented by the following formula (1). 0 <W1 / W2<1 ···(1) By satisfying the relationship of the above formula (1) and specifying W1 to be less than W2, the proportion of water-soluble components contained in the particulate copolymer is suppressed, and the above-mentioned mechanism tends to result in improved battery characteristics such as cycle characteristics and rate characteristics.

[0029] As a method for controlling the ratio of methacrylamide monomer units to 100 parts by mass of the total mass of vinyl monomer units in the particulate copolymer within the above-mentioned numerical range, for example, when carrying out emulsion polymerization as in the method for producing a particulate copolymer described below, a method of adjusting the compounding ratio of methacrylamide monomer to a value corresponding to a desired numerical range relative to the total compounding amount of vinyl monomers can be mentioned. In addition, as a method for controlling so as to satisfy the relationship of the formula (1), a method for adjusting the compounding ratio of the methacrylamide monomer and the acrylamide monomer to a value corresponding to a desired numerical range in the manufacturing method of the particulate copolymer constituting the binder for a nonaqueous secondary battery of this embodiment can be mentioned.

[0030] The content of the methacrylamide monomer unit and the acrylamide monomer unit contained in the particulate copolymer of the present embodiment when the total mass of the vinyl monomer unit is 100 parts by mass can be calculated from the blending ratio of the monomers when producing the particulate copolymer, or can be calculated from various spectrum data using IR (ATR method) etc. The amount of other monomer units contained in the particulate copolymer can be calculated by the same calculation method as that of the methacrylamide monomer unit.

[0031] (Storage modulus of particulate copolymer) As described above, in order to suppress the thermal shrinkage of the separator of the secondary battery even at high temperatures, for example, 150° C. or higher, it is preferable that the nonaqueous secondary battery binder of the present embodiment adheres sufficiently to the separator and the inorganic filler, and at the same time, the particulate copolymer has a high elastic modulus. Since the particulate copolymer contains an acrylamide monomer unit (B1) and a methacrylamide monomer unit (B2), the binder for non-aqueous secondary batteries of this embodiment has high adhesion from room temperature to high temperatures (e.g., 130°C) and maintains an excellent storage modulus E'.

[0032] The particulate copolymer contained in the binder for a nonaqueous secondary battery of the present embodiment has a storage modulus of 7×10 at 30° C. 6 Pa or more 5×108 Pa or less, and in the high temperature region, i.e., 130°C, it is 2 x 10 6 It is preferable that the pressure drop is equal to or higher than Pa. This tends to cause the coating layer containing the particulate copolymer to exhibit the above-mentioned behavior, and to suppress the separator having micropores from shrinking even when the separator is heated to a high temperature. The particulate copolymer has a storage modulus of 1×10 7 Pa or more 3×10 8 Pa or less and 5×10 at 130°C 6 It is more preferable that the pressure is 1 Pa or more. The particulate copolymer has a storage modulus of 4×10 at 30° C. 7 Pa or more 2×10 8 Pa or less and 6×10 6 It is more preferable that the pressure is 1 Pa or more. As a preferred embodiment of the binder for a non-aqueous secondary battery of the present embodiment, the particulate copolymer is a copolymer containing, as monomer units, one or more monomers selected from (meth)acrylic acid ester monomers, an acrylamide monomer, a methacrylamide monomer, a carboxylic acid group-containing monomer, and a crosslinkable monomer, the crosslinkable monomer containing an epoxy group-containing vinyl monomer, and the particulate copolymer has a storage modulus at 30° C. of 1×10 7 Pa or more 3×10 8 The storage modulus at 130°C is 5×10 6 The particulate copolymer having the above storage modulus is sometimes referred to as particulate copolymer I in this specification.

[0033] As a method for controlling the storage modulus of the particulate copolymer to satisfy the above range, a method for using a (meth)acrylamide monomer in the particulate copolymer can be mentioned. Also, as a method for further increasing the storage modulus of the particulate copolymer, a method for using an epoxy group-containing vinyl monomer can be mentioned. In this case, the vinyl monomer unit in the particulate copolymer contains an epoxy group-containing vinyl monomer unit. Furthermore, as a method for controlling the storage modulus of the particulate copolymer, there can be mentioned a method in which the copolymer contains one or more monomers selected from (meth)acrylic acid ester monomers, a carboxylic acid group-containing monomer, and a crosslinkable monomer as monomer units, and adjusts the types and mixing ratios of these monomers.

[0034] As described above, the content W2 of the methacrylamide monomer unit (B2) contained in the particulate copolymer of this embodiment is 2 parts by mass or more, more preferably 4 parts by mass or more, even more preferably 6 parts by mass or more, and even more preferably 10 parts by mass or more, per 100 parts by mass of the total mass of the vinyl monomer units. The upper limit of the proportion of the methacrylamide monomer is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, even more preferably less than 20 parts by mass, and even more preferably 15 parts by mass or less, per 100 parts by mass of the vinyl monomer unit mass. The content of the methacrylamide monomer units contained in the particulate copolymer is preferably 2 parts by mass or more and 20 parts by mass or less, more preferably 3 parts by mass or more and 15 parts by mass or less, and even more preferably 6 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the total mass of the vinyl monomer units. By making the content of methacrylamide monomer units 2 parts by mass or more, the particulate copolymer tends to have both high adhesion and storage modulus derived from hydrogen bonding force. Also, by making the content 20 parts by mass or less, the flexibility at room temperature is increased and the adhesion is improved.

[0035] <(Meth)acrylic acid ester monomer> As described above, in order to appropriately control the storage modulus of the particulate copolymer, it is effective to use one or more monomers selected from (meth)acrylic acid ester monomers in the particulate copolymer. The (meth)acrylic acid ester monomer is not limited to the following, but examples thereof include (meth)acrylic acid esters having one ethylenically unsaturated bond. In this specification, the (meth)acrylic acid ester may also be referred to as a (meth)acrylate. Examples of (meth)acrylic acid esters having one ethylenically unsaturated bond include, but are not limited to, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, t-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, cyclohexyl acrylate, methyl methacrylate (also referred to as methyl methacrylate in this specification), ethyl methacrylate, propyl methacrylate, ... (meth)acrylates having an alkyl group, such as isopropyl acrylate, butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, cyclohexyl methacrylate, isobornyl acrylate, and t-butylcyclohexyl acrylate; (meth)acrylates having an aromatic ring, such as benzyl acrylate, phenyl acrylate, benzyl methacrylate, and phenyl methacrylate; and the like. These (meth)acrylic acid ester monomers may be used alone or in combination of two or more. The (meth)acrylate having an alkyl group is preferably a (meth)acrylate comprising an alkyl group and a (meth)acryloyloxy group. The (meth)acrylate having an aromatic ring is preferably a (meth)acrylate comprising an aromatic ring and a (meth)acryloyloxy group.

[0036] The (meth)acrylic acid ester monomer is more preferably a (meth)acrylic acid ester monomer consisting of an alkyl group having 4 or more carbon atoms and a (meth)acryloyloxy group, even more preferably a (meth)acrylic acid ester monomer consisting of an alkyl group having 6 or more carbon atoms and a (meth)acryloyloxy group, even more preferably one or more selected from the group consisting of methyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, cyclohexyl methacrylate, isobornyl acrylate, and t-butylcyclohexyl acrylate, and even more preferably one or more selected from the group consisting of methyl methacrylate, cyclohexyl methacrylate, butyl acrylate, butyl methacrylate, and 2-ethylhexyl acrylate. The use of such a (meth)acrylic acid ester monomer is preferable from the viewpoint of improving the polymerization stability during emulsion polymerization and from the viewpoint of improving the adhesion to the electrode.

[0037] The (meth)acrylic acid ester monomer preferably contains at least methyl methacrylate. The content of methyl methacrylate is preferably 1.0 part by mass or more relative to 100 parts by mass of the total amount of the (meth)acrylic acid ester monomer. By containing 1.0 part by mass or more of methyl methacrylate relative to 100 parts by mass of the total amount of the (meth)acrylic acid ester monomer, the compatibility of the (meth)acrylic acid ester monomer and the (meth)acrylamide monomer is increased, and copolymerization is improved. In addition, the flexibility of the coating layer is increased at low temperatures (i.e., the peel strength between the separator and the coating layer using the binder for a non-aqueous secondary battery of this embodiment is increased), and the behavior of hardening the coating layer at high temperatures is more easily realized, and the shrinkage of the separator tends to be more suppressed even at high temperatures. The content of methyl methacrylate relative to 100 parts by mass of the total amount of (meth)acrylic acid ester monomers is more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more. The upper limit of the content of methyl methacrylate is not particularly limited, but may be 50 parts by mass or less, preferably 40 parts by mass or less, and more preferably 20 parts by mass or less.

[0038] <Carboxylic acid group-containing monomer> As described above, in order to appropriately control the storage modulus of the particulate copolymer, it is effective to use a carboxylic acid group-containing monomer in the particulate copolymer. The carboxylic acid group-containing monomer is not limited to the following, but may be, for example, an ethylenically unsaturated monomer having a carboxyl group. In this specification, the carboxylic acid group-containing monomer is also referred to as an unsaturated carboxylic acid. Examples of the ethylenically unsaturated monomer having a carboxyl group include, but are not limited to, monocarboxylic acid monomers such as acrylic acid, methacrylic acid, half ester of itaconic acid, half ester of maleic acid, and half ester of fumaric acid; dicarboxylic acid monomers such as itaconic acid, fumaric acid, and maleic acid; and the like. The carboxylic acid group-containing monomers can be used alone or in combination of two or more. Of these, acrylic acid, methacrylic acid, and itaconic acid are preferred, and acrylic acid and methacrylic acid are more preferred.

[0039] The content of the carboxylic acid group-containing monomer may be usually 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the vinyl monomer unit mass. From the viewpoint of further suppressing the shrinkage of the separator, the content of the carboxylic acid group-containing monomer is preferably 0.5 parts by mass or more and 5 parts by mass or less, more preferably 1 part by mass or more and 4 parts by mass or less, relative to 100 parts by mass of the vinyl monomer unit mass.

[0040] <Cross-linking monomer> As described above, in order to appropriately control the storage modulus of the particulate copolymer, it is effective to use a crosslinkable monomer. Examples of the crosslinkable monomer include a monomer having two or more radically polymerizable double bonds, and a monomer having a functional group that gives a self-crosslinking structure during or after polymerization. These may be used alone or in combination of two or more. The crosslinkable monomer constituting the particulate copolymer preferably contains an epoxy group-containing vinyl monomer. The epoxy group-containing vinyl monomer corresponds to a monomer having a functional group that gives a self-crosslinking structure during or after polymerization. Examples of the epoxy group-containing vinyl monomer include, but are not limited to, glycidyl acrylate, glycidyl methacrylate, allyl glycidyl ether, methyl glycidyl acrylate, and methyl glycidyl methacrylate. These may be used alone or in combination of two or more.

[0041] Examples of monomers having a functional group that gives a self-crosslinking structure during or after polymerization include, in addition to the above-mentioned epoxy group-containing vinyl monomers, hydroxyl group-containing vinyl monomers that contain a hydroxyl group, alkoxymethyl group-containing vinyl monomers that contain an alkoxymethyl group, and hydrolyzable silyl group-containing vinyl monomers that contain a hydrolyzable silyl group. These may be used alone or in combination of two or more.

[0042] As the crosslinkable monomer constituting the particulate copolymer, in addition to the epoxy group-containing vinyl monomer, it is preferable to further include at least one selected from the group consisting of a monomer having two or more radically polymerizable double bonds, an amino group-containing vinyl monomer, a hydroxyl group-containing vinyl monomer, an alkoxymethyl group-containing vinyl monomer, and a vinyl monomer having a hydrolyzable silyl group. By using the above-mentioned crosslinkable monomer, for example, when a non-aqueous secondary battery binder containing the particulate copolymer of this embodiment is used as an adhesive for electrodes or separators, the binder tends to have excellent adhesiveness while maintaining appropriate fluidity, and therefore excellent handleability.

[0043] Examples of monomers having two or more radically polymerizable double bonds include divinylbenzene and polyfunctional (meth)acrylates, etc. Among monomers having two or more radically polymerizable double bonds, polyfunctional (meth)acrylates are more preferred because they exhibit better resistance to electrolyte even in small amounts.

[0044] The polyfunctional (meth)acrylate may be a difunctional (meth)acrylate, a trifunctional (meth)acrylate, or a tetrafunctional (meth)acrylate. Examples of polyfunctional (meth)acrylates include, but are not limited to, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, and pentaerythritol tetramethacrylate, etc. These may be used alone or in combination of two or more. Among these, trimethylolpropane triacrylate and trimethylolpropane trimethacrylate are preferred because they exhibit better resistance to electrolyte even in small amounts.

[0045] The amino group-containing vinyl monomer is not limited to the following, but examples thereof include N,N-methylenebisacrylamide, diacetoneacrylamide, and N,N-dimethylaminoethylacrylamide.

[0046] Examples of the hydroxyl group-containing vinyl monomer include, but are not limited to, hydroxyethyl (meth)acrylates such as 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate; hydroxypropyl (meth)acrylates such as 2-hydroxypropyl (meth)acrylate; hydroxybutyl (meth)acrylates such as 2-hydroxybutyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; 3-chloro-2-hydroxypropyl (meth)acrylate, di-(ethylene glycol) maleate, di-(ethylene glycol) itaconate, 2-hydroxyethyl maleate, bis(2-hydroxyethyl) maleate, and 2-hydroxyethyl methyl fumarate. These hydroxyl group-containing vinyl monomers may be used alone or in combination of two or more. Examples of the hydroxyl group-containing vinyl monomer include, in addition to the above-mentioned compounds, methylol group-containing vinyl monomers. Examples of the methylol group-containing vinyl monomer include N-methylol acrylamide, N-methylol methacrylamide, dimethylol acrylamide, and dimethylol methacrylamide. These may be used alone or in combination of two or more.

[0047] Examples of the alkoxymethyl group-containing vinyl monomer include, but are not limited to, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, N-butoxymethylacrylamide, and N-butoxymethylmethacrylamide. These may be used alone or in combination of two or more.

[0048] Examples of the hydrolyzable silyl group-containing vinyl monomer include, but are not limited to, vinylsilane, vinyltrimethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-acryloxypropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, etc. These may be used alone or in combination of two or more.

[0049] The content of the monomer unit formed by the above-mentioned crosslinkable monomer is usually 2 parts by mass or more and 30 parts by mass or less, preferably 4 parts by mass or more and 25 parts by mass or less, more preferably 6 parts by mass or more and 25 parts by mass or less, and even more preferably 8 parts by mass or more and 25 parts by mass or less, relative to 100 parts by mass of the particulate copolymer. By setting the content of the monomer unit formed by the crosslinkable monomer in the range of 2 parts by mass or more and 30 parts by mass or less, the layer containing the particulate copolymer provided on the separator of the secondary battery tends to be able to better suppress the thermal shrinkage of the separator.

[0050] [Cross-linking monomer containing two or more vinyl groups] Among the above-mentioned crosslinkable monomers, it is preferable to use a crosslinkable monomer containing two or more vinyl groups. The content of the crosslinkable monomer unit containing two or more vinyl groups is preferably 0.1 parts by mass or more and 5 parts by mass or less, more preferably 0.3 parts by mass or more and 3 parts by mass or less, and even more preferably 0.5 parts by mass or more and 2 parts by mass, based on 100 parts by mass of the particulate copolymer. By setting the content of the crosslinkable monomer unit containing two or more vinyl groups to 0.1 parts by mass or more relative to 100 parts by mass of the particulate copolymer, the electrolyte resistance of the particulate copolymer can be improved. Also, by setting the content to 5 parts by mass or less, the binder for a nonaqueous secondary battery of this embodiment tends to have improved adhesion at room temperature and more effectively suppress the shrinkage of the separator even at high temperatures.

[0051] (Morphology of particulate copolymer) The particulate copolymer of the present embodiment may have the form of a dispersion in which, for example, a particulate copolymer (also called latex particles) containing the above-mentioned various monomers as monomer units is dispersed in an aqueous medium. Therefore, one embodiment of the non-aqueous secondary battery binder of this embodiment is an aqueous medium dispersion containing the particulate copolymer. The solid content concentration in the aqueous medium dispersion is not particularly limited, but is usually 10% by mass or more and 60% by mass or less, and preferably 30% by mass or more and 50% by mass or less. By making the solid content concentration 30% by mass or more, the degree of freedom in slurry design is increased, for example, by improving the dispersion stability due to the high solid content of the slurry. In addition, by making it 50% by mass or less, the viscosity of the aqueous medium dispersion containing the particulate copolymer is suppressed, and the workability in the slurry blending operation is improved.

[0052] (Viscosity of binder for non-aqueous secondary battery) The viscosity of the non-aqueous secondary battery binder of this embodiment is not particularly limited, but is usually 2000 mPas or less, and preferably 300 mPas or less. When the viscosity of the nonaqueous secondary battery binder of this embodiment is 2000 mPas or less, the handleability is improved, and for example, the workability in the slurry blending operation is improved. Usually, the viscosity of a non-aqueous secondary battery binder can be reduced to any value by adding adjustment water or the like. However, at the same time, the solid content concentration is reduced. Therefore, it is particularly preferable that the solid content concentration is at least 30 mass % and the above viscosity range is satisfied.

[0053] The binder for a non-aqueous secondary battery of this embodiment contains a particulate copolymer as particles (copolymer particles) dispersed in an aqueous medium. The aqueous medium dispersion may contain other solvents, dispersants, lubricants, thickeners, bactericides, etc. in addition to the aqueous medium and the copolymer.

[0054] (Glass transition temperature of particulate copolymer) The particulate copolymer contained in the binder for a nonaqueous secondary battery of this embodiment has an upper limit of the glass transition temperature of 10° C. or lower, preferably 0° C. or lower, and more preferably −5° C. or lower. The lower limit of the glass transition temperature is -50°C or higher, preferably -40°C or higher, and more preferably -30°C or higher. When the glass transition temperature is within the above range, the composition containing the nonaqueous secondary battery binder tends to be easily applied onto a separator of a secondary battery. The glass transition temperature can be controlled, for example, by adjusting the type and content of the monomer units constituting the particulate copolymer. Specifically, the glass transition temperature can be controlled within the above-mentioned numerical range by adjusting the content of the (meth)acrylic acid ester monomer and / or the unsaturated carboxylic acid. The glass transition temperature of the particulate copolymer can be measured by the method described in the above examples.

[0055] (Average particle size of particulate copolymer) The particulate copolymer has a volume average particle diameter Dv of preferably 30 nm or more and 230 nm or less, more preferably 50 nm or more and 200 nm or less, and further preferably 70 nm or more and 180 nm or less. When the volume average particle diameter Dv of the particulate copolymer is within the above range, when the lithium ion secondary battery adhesive using the nonaqueous secondary battery binder of this embodiment is adhered to a separator, a suitable amount of voids can be sufficiently left, and the function of the separator to allow ions in the electrolyte to pass through tends to be maintained. The volume average particle diameter Dv and number average particle diameter Dn of the particulate copolymer can be controlled, for example, by using a seed latex and a surfactant in a desired ratio when producing the copolymer. Usually, the volume average particle diameter Dv and number average particle diameter Dn tend to become smaller by increasing the amount of the seed latex and the surfactant used. The volume average particle diameter Dv and the number average particle diameter Dn can be measured by the method described in the examples below.

[0056] In the binder for nonaqueous secondary batteries of this embodiment, the ratio Dv / Dn of the volume average particle diameter Dv to the number average particle diameter Dn of the particulate copolymer is preferably 1 or more and 2.5 or less, more preferably 1 or more and 2 or less, and even more preferably 1 or more and 1.5 or less. The ratio Dv / Dn of the volume average particle diameter Dv to the number average particle diameter Dn is an index of the particle size distribution of the particulate copolymer. By making the ratio 2.5 or less, a dispersion with a narrow particle size distribution without coarse particles can be obtained, and when used as a coating layer, the structure becomes uniform, and high strength is achieved even at high temperatures, and the thermal shrinkage of the separator tends to be suppressed. By increasing the dispersion stability of the particulate copolymer in the aqueous medium during or after polymerization, the particle size distribution is narrowed and Dv / Dn can be controlled within the above-mentioned numerical range.As a method for increasing the dispersion stability, for example, a method of increasing the steric and electronic repulsion between the particulate copolymers by adding a surfactant to the aqueous medium during or after polymerization can be mentioned. The volume average particle diameter Dv and the number average particle diameter Dn can be measured by the method described in the examples described later.

[0057] (Method of producing particulate copolymer) The particulate copolymer used in the binder for a non-aqueous secondary battery of this embodiment can be produced by a known polymerization method, such as solution polymerization, emulsion polymerization, bulk polymerization, or the like.

[0058] In order to obtain the particulate copolymer as a dispersion, it is preferable to use an emulsion polymerization method as the polymerization method. The emulsion polymerization method is not particularly limited, and any conventionally known method can be used. An example of the emulsion polymerization method is a method in which, in an aqueous medium, an acrylamide monomer, a methacrylamide monomer, and, if necessary, a (meth)acrylic acid ester monomer, a carboxylic acid group-containing monomer, and a crosslinkable monomer are polymerized in a dispersion system having, as basic components, a radical polymerization initiator, a surfactant, and, if necessary, other additive components (e.g., a molecular weight regulator). In the polymerization, various methods can be used as necessary, such as a method in which the composition of the monomers supplied into the reaction system is kept constant throughout the entire polymerization process, or a method in which the composition of the monomers supplied is changed gradually or continuously during the polymerization process to change the composition of the particles of the resin dispersion produced. When the particulate copolymer is obtained by emulsion polymerization, for example, the obtained particulate copolymer may be in the form of an aqueous dispersion (latex) containing water and the particulate copolymer dispersed in the water.

[0059] As the (meth)acrylic acid ester monomer, the carboxylic acid group-containing monomer, and the crosslinkable monomer, the compounds described above can be used.

[0060] The radical polymerization initiator is capable of initiating addition polymerization of monomers by radical decomposition with heat or a reducing substance. As the radical polymerization initiator, either an inorganic initiator or an organic initiator can be used. As the radical polymerization initiator, a water-soluble or oil-soluble polymerization initiator can be used.

[0061] Examples of the water-soluble polymerization initiator include peroxodisulfates, peroxides, water-soluble azobis compounds, and peroxide-reducing agent redox systems. Examples of peroxodisulfates include potassium peroxodisulfate (KPS), sodium peroxodisulfate (NPS), and ammonium peroxodisulfate (APS). Examples of peroxides include hydrogen peroxide, t-butyl hydroperoxide, t-butyl peroxymaleic acid, succinic acid peroxide, and benzoyl peroxide. Examples of water-soluble azobis compounds include 2,2-azobis(N-hydroxyethylisobutyramide), 2,2-azobis(2-amidinopropane) dihydrochloride, and 4,4-azobis(4-cyanopentanoic acid). Examples of peroxide-reducing agent redox systems include those in which the above-mentioned peroxides are combined with one or more reducing agents such as sodium sulfoxylate formaldehyde, sodium hydrogen sulfite, sodium thiosulfate, sodium hydroxymethanesulfinate, L-ascorbic acid and its salts, cuprous salts, and ferrous salts.

[0062] The radical polymerization initiator can be used in an amount of preferably 0.05 to 0.4 parts by mass based on 100 parts by mass of the total amount of monomers.

[0063] The surfactant forms micelles in an aqueous medium to provide a polymerization field for the polymerizable monomers, and also imparts dispersion stability by adsorbing to the surface of the particulate copolymer. The ionic species of the surfactant may be nonionic, anionic or cationic. From the viewpoint of dispersion stability, it is preferable that the surfactant has a nonionic or anionic species or both. The surfactant may have a radically polymerizable unsaturated double bond (e.g., a vinyl group) in its molecular structure. A surfactant having a radically polymerizable unsaturated double bond in its molecular structure is hereinafter referred to as a reactive surfactant.

[0064] Examples of nonionic surfactants that are nonreactive surfactants include, but are not limited to, nonreactive polyoxyethylene alkyl ethers, polyoxyalkylene alkyl ethers, polyoxyethylene polycyclic phenyl ethers, polyoxyethylene distyrenated phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerin fatty acid esters, polyoxyethylene fatty acid esters, polyoxyethylene alkylamines, alkyl alkanolamides, and polyoxyethylene alkyl phenyl ethers.

[0065] Examples of anionic surfactants that are non-reactive surfactants include, but are not limited to, non-reactive alkyl sulfates, polyoxyethylene alkyl ether sulfate salts, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, naphthalene sulfonate-formaldehyde condensates, polyoxyethylene polycyclic phenyl ether sulfate salts, polyoxyethylene distyrenated phenyl ether sulfate salts, fatty acid salts, alkyl phosphates, and polyoxyethylene alkyl phenyl ether sulfate salts.

[0066] The anionic reactive surfactant which is a reactive surfactant is not limited to the following, but for example, an ethylenically unsaturated monomer having a sulfonic acid group, a sulfonate group, or a sulfate ester group, or a salt thereof, and a compound having a sulfonic acid group or a group which is an ammonium salt or an alkali metal salt thereof (an ammonium sulfonate group, or an alkali metal sulfonate group) is preferred. Examples of such anionic reactive surfactants include, but are not limited to, alkyl allyl sulfosuccinates (e.g., Sanyo Chemical Industries, Ltd.'s "ELEMINOL(TM) JS-2" and "ELEMINOL(TM) JS-5"; Kao Corporation's "LATEMUL(TM) S-120", "LATEMUL(TM) S-180A", "LATEMUL(TM) S-180", etc.); polyoxyethylene alkyl propenyl phenyl ether sulfates (e.g., Daiichi Kogyo Seiyaku Co., Ltd.'s "AQUALON(TM) SR-10" and "AQUALON(TM) SR-1025", etc.); ammonium α-sulfonato-ω-1-(allyloxymethyl) alkyloxy polyoxyethylenes (e.g., Daiichi Kogyo Seiyaku Co., Ltd.'s "AQUALON KH-1025", etc.); and the like.

[0067] Examples of nonionic reactive surfactants that are reactive surfactants include, but are not limited to, α-[1-[(allyloxy)methyl]-2-(nonylphenoxy)ethyl]-ω-hydroxypolyoxyethylene (for example, ADEKA REASOAP NE-20, ADEKA REASOAP NE-30, ADEKA REASOAP (trademark) NE-40, etc., manufactured by Asahi Denka Kogyo Co., Ltd.); polyoxyethylene alkylpropenyl phenyl ether (for example, AQUALON (trademark) RN-10, AQUALON (trademark) RN-20, AQUALON (trademark) RN-30, AQUALON (trademark) RN-50, etc., manufactured by Daiichi Kogyo Seiyaku Co., Ltd.); and the like.

[0068] The surfactant used in the polymerization step of the particulate copolymer preferably contains a reactive surfactant. The reactive surfactant may be used alone or in combination of two or more kinds. The particulate copolymer contained in the binder for non-aqueous secondary batteries of this embodiment preferably has a vinyl monomer unit and a monomer unit derived from a reactive surfactant having a functional group copolymerizable with a vinyl group, and therefore, as the reactive surfactant, it is preferable to use one that has excellent copolymerizability with a vinyl compound. From this viewpoint, for example, polyoxyethylene alkylpropenylphenyl ether sulfate ester salt (e.g., "Aqualon (trademark) SR-1025" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., etc.) is preferable, and ammonium = α-sulfonato-ω-1-(allyloxymethyl) alkyloxy polyoxyethylene (e.g., "Aqualon KH-1025" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., etc.) is preferable. These are preferably used because the steric repulsion of the polyoxyethylene group and the electronic repulsion due to the anionic nature of the sulfonate ester group are effective in improving the stability of the particulate copolymer during and / or after polymerization.

[0069] The reactive surfactant is effective in enhancing copolymerization of the acrylamide monomer, the methacrylamide monomer, and other vinyl monomers, and in producing a copolymer having a uniform composition distribution. The presumed mechanism is as follows. First, a polymer extension reaction starts between a part of the methacrylamide monomer dissolved in water and a reactive surfactant. The growing polymer radical forms a micelle, into which the remaining methacrylamide monomer and other vinyl monomers penetrate, and the copolymer grows. By the above mechanism, the formation of a water-soluble copolymer derived from homopolymerization of methacrylamide monomer is suppressed, and copolymerization with other vinyl monomers can proceed. It is important that the copolymer composition is uniform and that the production of a water-soluble copolymer is suppressed in order to increase the storage modulus of the particulate copolymer and to prevent a decrease in battery performance due to clogging when the particulate copolymer is applied to a separator as a slurry. From the viewpoint of the opportunity for contact with the methacrylamide monomer in the aqueous layer, it is particularly preferable to use an anionic reactive surfactant.

[0070] The molecular weight regulator is not limited to the following, but may be any of those usable in normal emulsion polymerization, including halogenated hydrocarbons such as chloroform and carbon tetrachloride, mercaptans such as n-hexymercaptan, n-octylmercaptan, n-dodecylmercaptan, t-dodecylmercaptan, and thioglycolic acid, xanthogens such as dimethylxanthogen disulfide and diisopropylxanthogen disulfide, terpinolene, α-methylstyrene dimer, etc. Among these, n-dodecylmercaptan is preferably used.

[0071] The amount of the molecular weight modifier used is preferably 5 parts by mass or less per 100 parts by mass of the total amount of monomers used when polymerizing each part.

[0072] [Adhesive for lithium-ion secondary batteries] The binder for a nonaqueous secondary battery of this embodiment is used as an adhesive for a lithium ion secondary battery. The adhesive for lithium ion secondary batteries is used, for example, to bond a separator and an electrode. The adhesive for lithium ion secondary batteries is used, for example, when forming an adhesive layer on a separator or an electrode of a lithium ion secondary battery. In particular, a separator with an adhesive layer for lithium ion secondary batteries can be manufactured by applying the adhesive for lithium ion secondary batteries onto a separator and forming an adhesive layer. For more detailed configuration of the lithium ion secondary battery, reference can be made to, for example, those described in JP 2015-41603 A.

[0073] [Binder for porous layer in non-aqueous secondary battery] The binder for a non-aqueous secondary battery of this embodiment can be suitably used as a binder for a porous layer in a non-aqueous secondary battery. The binder for the porous layer is used, for example, when forming a porous layer on a separator by bonding inorganic fillers or the like by point adhesion, thereby improving the heat resistance of the separator while maintaining the permeability of lithium ions.

[0074] [Slurry for Lithium Ion Secondary Battery Porous Layer] The slurry for a lithium ion secondary battery porous layer of this embodiment contains water, an inorganic filler, and the binder for a nonaqueous secondary battery of this embodiment.

[0075] The slurry for the lithium ion secondary battery porous layer of this embodiment is a dispersion liquid used for forming a porous layer containing an inorganic filler and a particulate copolymer on the substrate by applying the slurry to, for example, a surface of a separator substrate for an electric storage device and then drying the slurry. The slurry for the lithium ion secondary battery porous layer of this embodiment may contain a conductive assistant, a thickener, a non-aqueous solvent, etc., as necessary.

[0076] [Porous layer of lithium ion secondary battery] The lithium ion secondary battery porous layer of the present embodiment contains an inorganic filler and the binder for a nonaqueous secondary battery of the present embodiment.

[0077] (Inorganic filler) The inorganic filler used in the lithium ion secondary battery porous layer is not particularly limited, but it is preferable that the inorganic filler has a melting point of 200°C or higher, has high electrical insulation properties, and is electrochemically stable within the range of use of the lithium ion secondary battery.

[0078] Examples of inorganic fillers include, but are not limited to, oxide ceramics such as alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, barium sulfate, magnesium sulfate, aluminum sulfate, aluminum hydroxide, aluminum oxide hydroxide, potassium titanate, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These may be used alone or in combination of two or more.

[0079] Among these, from the viewpoint of improving the electrochemical stability and heat resistance of the separator, it is preferable to use aluminum oxide compounds such as alumina, aluminum hydroxide, and aluminum oxide hydroxide (AlO(OH)); and aluminum silicate compounds having no ion exchange capacity such as kaolinite, dickite, nacrite, halloysite, and pyrophyllite, or barium sulfate.

[0080] Alumina has many crystal forms, such as α-alumina, β-alumina, γ-alumina, and θ-alumina, and any of these can be suitably used. Among these, α-alumina is preferred from the viewpoint of thermal and chemical stability.

[0081] As the aluminum oxide compound, aluminum oxide hydroxide (AlO(OH)) is preferred. As the aluminum oxide hydroxide, boehmite is more preferred from the viewpoint of preventing internal short circuit caused by the generation of lithium dendrites. By adopting particles mainly composed of boehmite as the inorganic filler constituting the lithium ion secondary battery porous layer of this embodiment, a lithium secondary battery porous layer that is very light while maintaining high permeability can be obtained, and even when a thinner lithium ion secondary battery porous layer is formed, the thermal shrinkage of the separator at high temperatures is suppressed, and excellent heat resistance tends to be exhibited. Synthetic boehmite, which can reduce ionic impurities that adversely affect the characteristics of electrochemical devices, is more preferred.

[0082] As the aluminum silicate compound having no ion exchange capacity, kaolin, which is mainly composed of kaolin mineral, is more preferable because it is inexpensive and easily available. Kaolin includes wet kaolin and calcined kaolin obtained by calcining wet kaolin. In this embodiment, calcined kaolin is more preferable. Calcined kaolin tends to have excellent electrochemical stability because water of crystallization is released during the calcination process and impurities are also removed.

[0083] The average particle size of the inorganic filler used in the lithium ion secondary battery porous layer is preferably more than 0.01 μm and not more than 2.0 μm, more preferably more than 0.1 μm and not more than 1.5 μm, and even more preferably more than 0.2 μm and not more than 1.0 μm. It is preferable to set the average particle size of the inorganic filler within the above range from the viewpoint of suppressing the thermal shrinkage of the separator at high temperatures even when the thickness of the porous layer is thin (for example, 4 μm or less). As a method for adjusting the average particle size and its distribution of the inorganic filler, for example, a method of reducing the particle size by pulverizing the inorganic filler using an appropriate pulverizing device such as a ball mill, a bead mill, or a jet mill can be mentioned.

[0084] Examples of the shape of the inorganic filler include plate-like, scaly, needle-like, columnar, spherical, polyhedral, block-like, etc. A combination of inorganic fillers having these shapes may be used.

[0085] The proportion of the inorganic filler in the lithium ion secondary battery porous layer of this embodiment can be appropriately determined from the viewpoints of the binding property of the inorganic filler, the permeability of the separator, heat resistance, etc. The proportion of the inorganic filler in the lithium ion secondary battery porous layer is preferably 20 parts by mass or more and less than 100 parts by mass, more preferably 50 parts by mass or more and 99.99 parts by mass or less, still more preferably 80 parts by mass or more and 99.9 parts by mass or less, and even more preferably 90 parts by mass or more and 99.5 parts by mass or less, when the total of the inorganic filler and the particulate copolymer is 100 parts by mass.

[0086] The thickness of the lithium ion secondary battery porous layer of this embodiment is preferably 0.5 μm or more from the viewpoint of improving heat resistance and insulation properties, and is preferably 4 μm or less from the viewpoint of increasing the capacity and improving the permeability of the battery.

[0087] The layer density of the lithium ion secondary battery porous layer of this embodiment is 0.5 g / cm 3 More than 3.0g / cm 3 It is preferable that the concentration is 1.0 g / cm or less. 3 More than 2.5g / cm 3 It is more preferable that the layer density of the lithium ion secondary battery porous layer of the present embodiment is 0.5 g / cm or less. 3 When the layer density of the porous layer of the lithium ion secondary battery of this embodiment is 3.0 g / cm or more, the thermal shrinkage rate at high temperatures tends to be good. 3 When the thickness is less than 100 mm, the air permeability tends to decrease.

[0088] The method for forming the lithium ion secondary battery porous layer of the present embodiment may include, for example, a method for applying a coating liquid containing an inorganic filler and the non-aqueous secondary battery binder of the present embodiment to at least one surface of a porous substrate constituting a separator. In this case, the coating liquid may contain a solvent, a dispersant, a thickener, etc., in order to improve dispersion stability, coatability, and storage property.

[0089] [Separator for lithium ion secondary battery] The lithium ion secondary battery separator (separator) of this embodiment includes the lithium ion secondary battery porous layer of this embodiment. The separator can include a porous substrate and a porous layer disposed on at least a portion of at least one side of the porous substrate. The porous layer is the lithium ion secondary battery porous layer of this embodiment, and contains the particulate copolymer described above. This separator may be composed only of a porous substrate and the lithium ion secondary battery porous layer of this embodiment, or may further have an adhesive layer for bonding to the electrodes.

[0090] When the lithium ion secondary battery separator has a lithium ion secondary battery porous layer, the porous layer is disposed on one or both sides of the porous substrate of the separator.

[0091] Each member constituting the separator and a preferred embodiment of a method for producing the separator will be described in detail below.

[0092] (Porous base material) The porous substrate is a substrate having pores or gaps therein, and the porous substrate may be one that has been used as a separator for a secondary battery. As the porous substrate, a polyolefin microporous film containing a polyolefin resin as a main component is preferable from the viewpoint of providing excellent coating properties when a porous layer is formed through a coating process, and from the viewpoint of making the thickness of the separator thinner and increasing the active material ratio in a battery or other storage device to increase the capacity per volume. Here, "containing as a main component" means containing more than 50% by mass, preferably 75% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and may be 100% by mass.

[0093] The surface of the polyolefin microporous membrane is preferably subjected to a surface treatment, since this makes it easier to apply a coating liquid thereafter and improves the adhesion between the polyolefin microporous membrane and the porous layer. Examples of the surface treatment method include a corona discharge treatment method, a plasma treatment method, a mechanical roughening method, a solvent treatment method, an acid treatment method, and an ultraviolet oxidation method.

[0094] (Method of arranging porous layer of lithium ion secondary battery containing inorganic filler) The lithium ion secondary battery porous layer of this embodiment can be disposed on a porous substrate by, for example, applying a coating liquid containing an inorganic filler, a particulate copolymer, and, if necessary, additional components such as a solvent (e.g., water) and a dispersant to at least one surface of the porous substrate. The particulate copolymer may be synthesized by emulsion polymerization, and the resulting emulsion may be used as it is as a coating liquid. The coating liquid preferably contains a poor solvent for the particulate copolymer, such as water or a mixed solvent of water and a water-soluble organic medium (for example, methanol or ethanol).

[0095] The method for applying the coating liquid to the porous substrate of the separator is not particularly limited as long as the required layer thickness and coating area can be achieved. Examples of the coating method include gravure coater method, small diameter gravure coater method, reverse roll coater method, transfer roll coater method, kiss coater method, dip coater method, knife coater method, air doctor coater method, blade coater method, rod coater method, squeeze coater method, cast coater method, die coater method, screen printing method, spray coating method, inkjet coating method, etc. In particular, the gravure coater method is preferred because it has a high degree of freedom in the coating shape.

[0096] The method for removing the solvent from the coating film after coating is not limited as long as it does not adversely affect the porous substrate and the lithium ion secondary battery porous layer. For example, a method of drying the substrate at a temperature below the melting point of the substrate while fixing the substrate, a method of drying under reduced pressure at a low temperature, etc. can be mentioned.

[0097] The method for removing the solvent from the coating film after coating is not particularly limited as long as it does not adversely affect the porous substrate and the lithium ion secondary battery porous layer. For example, a method of drying the polyolefin porous substrate at a temperature below its melting point while fixing it, a method of drying under reduced pressure at a low temperature, a method of immersing the substrate in a poor solvent for the particulate copolymer to solidify the particulate copolymer into particles and simultaneously extracting the solvent, etc. can be mentioned.

[0098] [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes the lithium ion secondary battery separator of this embodiment. The lithium ion secondary battery of the present embodiment may have a configuration similar to that of a conventionally known lithium ion secondary battery, for example, as described in JP 2018-92701 A, except that it includes the separator of the present embodiment.

[0099] The particulate copolymer used in the binder for a non-aqueous secondary battery of this embodiment can be contained in a porous layer on a separator, and a film including the separator and the porous layer is called a coating film. The heat shrinkage rate of the coating film at 150° C. is not particularly limited, but is preferably 0% or more and less than 40%, more preferably 0% or more and 35% or less, and even more preferably 0% or more and 30% or less, in both MD and TD. By having the heat shrinkage rate at 150° C. be 30% or less in both MD and TD, the separator can be prevented from rupturing even when the battery abnormally heats up, contact between the positive and negative electrodes can be suppressed, and better safety performance tends to be obtained. EXAMPLES

[0100] Hereinafter, the present embodiment will be described in more detail using examples and comparative examples, but the present invention is not limited to the following examples in any way. Various physical properties were measured and evaluated by the following measuring and evaluating methods.

[0101] [Solid content concentration] About 1 g of the aqueous dispersion of the particulate copolymer obtained in the examples and comparative examples described below was precisely weighed out on an aluminum dish, and the weight (g) of the aqueous dispersion weighed out was designated as a. This was dried in a hot air dryer at 130°C for 1 hour, and the dry weight (g) of the copolymer after drying was designated as b. The solid concentration was calculated according to the following formula. Solid content concentration (%)=b / a×100

[0102] [pH of water dispersion of particulate copolymer] The electrodes of a pH meter (glass electrode type hydrogen ion concentration indicator, manufactured by DDK Toa Corp.) were immersed in an aqueous dispersion of the particulate copolymer having a solid content concentration of about 40%, and the displayed value was read.

[0103] [Glass transition temperature of particulate copolymer] An appropriate amount of the particulate copolymer-containing aqueous dispersion (solid concentration 38 to 42%, pH 8.0) obtained in the Examples and Comparative Examples described below was placed on an aluminum dish and dried in a hot air dryer at 130° C. for 60 minutes. Approximately 17 mg of the dried film after drying was placed in an aluminum container for measurement, and a DSC curve and a DDSC curve were obtained under a nitrogen atmosphere using a DSC measurement device (Shimadzu Corporation, model number: DSC6220). The measurements were carried out according to the following program. (1st stage heating program) The temperature started at 70°C and was increased at a rate of 15°C per minute. After reaching 110°C, it was maintained for 5 minutes. (2nd stage cooling program) The temperature was decreased from 110°C at a rate of 30°C per minute. After reaching -50°C, it was maintained at this temperature for 4 minutes. (Third stage heating program) The temperature was increased from -50°C to 130°C at a rate of 15°C per minute. DSC and DDSC data were collected during this third temperature increase. The glass transition temperature (Tg) was determined as the intersection point between a straight line extending from the baseline of the obtained DSC curve to the higher temperature side and a tangent to the inflection point.

[0104] [Average particle size of particulate copolymer] The 50% particle size (μm) was measured using a particle size measuring device based on a light scattering method (manufactured by LEED & NORTHRUP, trade name "MICROTRAC UPA150"), and this was taken as the average particle size. In this way, the number average particle size (Dn) and the volume average particle size (Dv) were obtained, and the ratio thereof, Dv / Dn, was calculated.

[0105] [Electrolyte swelling rate] 3 g of the aqueous dispersion (solid content concentration 38-42%, pH 8.0) containing the particulate copolymer obtained in the examples and comparative examples described below was taken on an aluminum dish and dried for 60 minutes in a hot air dryer at 130 ° C. The dried film was cut to 0.5 g and placed in a 50 mL vial together with 10 g of a mixed solvent of ethylene carbonate: ethyl methyl carbonate = 1: 2 (volume ratio), and shaken for 3 hours, after which the sample was taken out and washed with the mixed solvent, and the mass (Wa) was measured. After that, the sample was left to stand in an oven at 150 ° C. for 1 hour, and the mass (Wb) was measured, and the swelling degree of the particulate copolymer with respect to the electrolyte was measured by the following formula. Although the mixed solvent does not contain an electrolyte, it was confirmed that there was no difference in the degree of swelling of the particulate copolymer regardless of the presence or absence of an electrolyte. Swelling degree of particulate copolymer in electrolyte (times) = (Wa-Wb) / Wb

[0106] [Viscosity, slurry blending workability, solution stability] 100 g of the aqueous dispersion (solid content concentration 30 to 42%, pH 5.0) containing the particulate copolymer obtained in the examples and comparative examples described below was weighed out into a polypropylene bottle, and the viscosity was measured using a BM type viscometer (TV-100B manufactured by Toki Sangyo Co., Ltd.) at a spindle rotation speed of 60 rpm (initial viscosity: ηi). Thereafter, the sample was stored in a thermostatic chamber maintained at 60° C. for 2 weeks, and then the viscosity was measured again under the same conditions as above using the BM type viscometer (viscosity after storage: ηf). Using these measured values, the slurry blending workability and solution stability were evaluated according to the following criteria. <Evaluation Criteria for Slurry Blending Workability> A: ηi is less than 300mPa·s B: ηi is 300 mPa·s or more and less than 2000 mPa·s C: ηi is 2000mPa·s or more <Evaluation Criteria for Solution Stability> A: ηf / ηi is 0.8 or more and less than 2.0 B: ηf / ηi is 0.5 or more and less than 0.8 or 2.0 or more and less than 3.0 C: ηf / ηi is less than 0.5 or 3.0 or more

[0107] [Storage modulus] The storage modulus of the particulate copolymer was measured in accordance with JIS K 7244. Approximately 12 g of the aqueous dispersion (solid content concentration 40%) of the particulate copolymer obtained in the Examples and Comparative Examples described below was poured onto a polypropylene plate divided into 15 cm squares and dried at room temperature for one day. The resulting polymer film was molded into a 5 mm x 70 mm square to prepare a test specimen. The thickness of the obtained test piece was recorded as the average value of three points, namely, the center of the sample and points ±20 mm away from the center in the long side direction, using a film thickness meter (DIGIMATIC INDICATOR, manufactured by MITSUTOYO). The tensile storage modulus was measured using a viscoelasticity measuring device (manufactured by Rheometric Scientific, product name RSA3) in tension-compression mode with a chuck distance of 50 mm, an initial temperature of 30°C, an end temperature of 140°C, a heating rate of 5°C / min, 1.0 Hz, and a strain of 0.1%, to obtain the storage modulus at 30°C and the storage modulus at 130°C. In the following Tables 1 to 6, the storage modulus "E+a" is expressed as x 10 a This means that.

[0108] [Adhesion (peel strength)] A dispersion for forming a porous layer was obtained by using the aqueous dispersion of the particulate copolymer obtained in the Examples and Comparative Examples described later and following the procedure described later (Formation of a coating film). The dispersion for forming a porous layer was applied to the surface of a corona-treated porous polyethylene substrate, followed by drying to form a porous layer, thereby obtaining a coating film having a total thickness of 17 μm. This coating film was attached to a 15 mm×75 mm preparation with double-sided tape so that the polyethylene porous substrate side was adhered. Then, a 12 mm wide mending tape was applied onto the porous layer, and one end of the mending tape was pulled vertically at a pulling speed of 100 mm / min to measure the stress when peeled off. The measurement was carried out three times, and the average value was calculated and used as the peel strength. The larger the peel strength value, the better the adhesion between the polyethylene porous substrate and the porous layer. The peel strength was evaluated according to the following criteria. <Adhesion Evaluation Criteria> A:300gf / cm or more B: 150gf / cm or more and less than 300gf / cm C: Less than 150gf / cm

[0109] [Heat shrink resistance] A coating film was obtained using the aqueous dispersion of the particulate copolymer obtained in the Examples and Comparative Examples described below, and according to the (Formation of Coating Film) described below. A 100 mm piece was cut in the MD direction and a 100 mm piece in the TD direction, and left to stand in an oven at 150°C for 1 hour. The sample was sandwiched between two pieces of paper to prevent hot air from directly hitting the sample. After removing the sample from the oven and cooling, the length (mm) was measured and the thermal shrinkage was calculated using the following formula. The measurements were carried out in the MD and TD directions, and the larger value was taken as the heat shrinkage rate, and the heat shrinkage resistance was evaluated according to the following criteria. Heat shrinkage rate (%) = {(100 - length after heating) / 100} x 100 <Evaluation Criteria for Heat Shrinkage Resistance> A: Heat shrinkage rate less than 3% B: Heat shrinkage rate 3% or more and less than 10% C: Heat shrinkage rate 10% or more

[0110] [Separator moisture content] Using the aqueous dispersions of the particulate copolymers obtained in the Examples and Comparative Examples described below, and following the procedure described below (Formation of the coating film), separators having a porous layer were obtained. The separator was cut into pieces weighing 0.15 g to 0.20 g and pretreated at 23° C. and a relative humidity of 40% for 12 hours. Thereafter, the mass was measured and used as the sample mass (g). The moisture mass (μg) of the sample after pretreatment was measured using a Karl Fischer device. The heating and vaporization conditions during the measurement were 150°C and 10 minutes. Hydranal Coulomat CG-K (manufactured by SIGMA-ALDRICH) was used as the cathode reagent, and Hydranal Coulomat AK (manufactured by SIGMA-ALDRICH) was used as the anode reagent. The moisture content of the separator was calculated according to the following formula and evaluated according to the following criteria. Moisture content of separator W (ppm) = moisture mass (μg) / sample mass (g) <Evaluation Criteria for Moisture Content of Separator> A:W is less than 800ppm B:W is between 800ppm and 1500ppm C:W is 1500ppm or more

[0111] [Characteristics of small batteries (rate characteristics)] <Preparation of positive electrode> LiNi as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 The mixture was mixed with carbon black as a conductive assistant and a polyvinylidene fluoride solution as a binder in a solid content mass ratio of 91:5:4, and N-methyl-2-pyrrolidone was added as a dispersion solvent so that the solid content was 68 mass %, and further mixed to prepare a slurry solution. This slurry solution was applied to one side of an aluminum foil with a thickness of 15 μm so that part of the aluminum foil was exposed, and then the solvent was dried and removed to obtain a coating amount of 175 g / m. 2 Furthermore, the density of the positive electrode mixture was 2.8 g / cm 3 The coated area was then cut to a size of 30 mm×50 mm and to include an exposed portion of the aluminum foil, and an aluminum lead piece was welded to the exposed portion of the aluminum foil to obtain a positive electrode. <Preparation of negative electrode> Artificial graphite was mixed as the negative electrode active material, and styrene butadiene rubber and a carboxymethyl cellulose aqueous solution were mixed as the binder in a solid content mass ratio of 96.4:1.9:1.7, and water was added as a dispersion solvent so that the solid content was 50 mass %, and further mixed to prepare a slurry solution. This slurry solution was applied to one side of a copper foil with a thickness of 10 μm so that part of the copper foil was exposed, and then the solvent was dried and removed to obtain a coating amount of 86 g / m. 2 Furthermore, the density of the negative electrode mixture was 1.45 g / cm 3 The coated area was then cut to a size of 32 mm × 52 mm and to include the exposed copper foil area, and a nickel lead piece was welded to the exposed copper foil area to obtain a negative electrode. <Preparation of non-aqueous electrolyte> In a mixed solvent of ethylene carbonate:ethyl methyl carbonate = 1:2 (volume ratio), LiPF 6The above was dissolved to a concentration of 1.0 mol / L, and vinylene carbonate was further added to a concentration of 1.0 mass % to prepare a nonaqueous electrolyte solution. <Cell assembly> Using the aqueous dispersion of the particulate copolymer obtained in the examples and comparative examples described below, and following the procedure described below (Formation of the coating film), a separator having a porous layer was obtained. The separator was cut into a 60 mm × 40 mm square. The positive electrode, separator, and negative electrode were stacked in this order to form a laminate. At this time, the porous layer side of the coating film obtained in the process described later (Formation of the coating film) was placed facing the positive electrode. This laminate was inserted into an aluminum laminate exterior body measuring 80 mm x 60 mm. Next, the non-aqueous electrolyte was poured into the exterior body, and the opening was then sealed to prepare a small battery.

[0112] The assembled small battery was charged at 25°C with a constant current of 2 mA (approximately 0.05 C) up to a battery voltage of 4.2 V, and then charged for a total of approximately 21 hours with constant voltage charging to maintain 4.2 V, after which it was discharged at a current value of 7 mA down to a battery voltage of 3.0 V. It was then charged with a constant current of 12 mA (approximately 0.3 C) up to a battery voltage of 4.2 V, and then charged with constant voltage charging to maintain 4.2 V for a total of approximately 5 hours, after which it was discharged at a current value of 12 mA down to a battery voltage of 3.0 V, three times.

[0113] Next, at 25°C, the battery was charged at a constant current of 12 mA (approximately 0.3 C) up to a battery voltage of 4.2 V, and then further charged for a total of 5 hours with constant voltage charging to maintain 4.2 V. After that, the battery was discharged at a current value of 36 mA (approximately 1.0 C) down to a battery voltage of 3.0 V, and the discharge capacity at that time was recorded as the 1C discharge capacity (mAh).

[0114] Next, the battery was charged at 25°C with a constant current of 12 mA (approximately 0.3 C) up to a battery voltage of 4.2 V, and then further charged with a constant voltage charge maintaining 4.2 V for a total of approximately 5 hours. After that, the battery was discharged at a current value of 72 mA (approximately 2.0 C) down to a battery voltage of 3.0 V, and the discharge capacity at that time was recorded as the 2C discharge capacity (mAh).

[0115] The ratio of the 2C discharge capacity to the 1C discharge capacity was calculated, and this value was taken as the rate characteristic and evaluated according to the following criteria. Rate characteristic (%) = (2C discharge capacity / 1C discharge capacity) x 100

[0116] <Rate characteristic evaluation criteria> A: Rate characteristics 90% or more B: Rate characteristics 80% or more and less than 90% C: Rate characteristics less than 80%

[0117] [Cycle characteristics] The small battery whose rate characteristics had been evaluated as described above was charged at 60°C with a current value of 6 mA (approximately 1.0 C) up to a battery voltage of 4.2 V. After reaching 4.2 V, the voltage was maintained at 4.2 V while adjusting the current value for a total of 3 hours of charging. The battery was then discharged at a current value of 6 mA down to a battery voltage of 3.0 V. This cycle was repeated 100 times, and the discharge capacity (mAh) at the 1st and 100th cycles was measured. The ratio of the discharge capacity at the 100th cycle to the discharge capacity at the first cycle was calculated, and this value was taken as the cycle characteristic, which was evaluated according to the following criteria. Cycle characteristic (%) = (100th discharge capacity / 1st discharge capacity) x 100 <Evaluation criteria for cycle characteristics> A: 90% or more B: 80% or more but less than 90% C: Less than 80%

[0118] [Example 1] (Production of particulate copolymer) A reaction vessel equipped with a stirrer, a reflux condenser, a dropping tank, and a thermometer was charged with 65 parts by mass of ion-exchanged water and, as surfactants, 0.06 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., also referred to as "KH1025") and 0.06 parts by mass of "Adeka Reasoap SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation, also referred to as "SR1025"). Next, the temperature inside the reaction vessel was raised to 75° C., and 1.5 parts by mass of a 2% aqueous solution of ammonium persulfate (also referred to as "APS") was added while maintaining the temperature at 75° C. Five minutes after the addition of the aqueous ammonium persulfate solution was completed, the following emulsion was dropped from the dropping tank into the reaction vessel over 150 minutes. The emulsion was prepared by the following method. (Meth)acrylic acid esters as monomers; Methyl methacrylate (also referred to as "MMA") 6.4 parts by mass, Butyl acrylate (also referred to as "BA") 42 parts by weight, 34 parts by mass of 2-ethylhexyl acrylate (also referred to as "2EHA"); 60 parts by weight of 2-hydroxyethyl methacrylate (also referred to as "HEMA"), As unsaturated carboxylic acids; 1 part by mass of methacrylic acid (also referred to as "MAA"); 1.5 parts by mass of acrylic acid (also referred to as "AA"), (Meth)acrylamide as a monomer; 0.1 parts by mass of acrylamide (also referred to as "AAm"), Methacrylamide (also referred to as "MAAm") 7 parts by weight As an epoxy group-containing monomer; 2 parts by weight of glycidyl methacrylate (also referred to as "GMA"); As a crosslinking monomer containing two or more vinyl groups; 2 parts by mass of trimethylolpropane triacrylate (ATMPT, product name of Shin-Nakamura Chemical Co., Ltd., also referred to as "A-TMPT"), As a reactive surfactant; "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 7.5 parts by mass, 7.5 parts by weight of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution made by ADEKA Corporation), As a polymerization initiator; 0.25 parts by weight of a 2% aqueous solution of ammonium persulfate, and 83.2 parts by mass of ion-exchanged water, The mixture was mixed for 5 minutes using a homomixer. After the dropwise addition of the emulsifying liquid was completed, the temperature inside the reaction vessel was raised to 80° C. and maintained at that temperature for 120 minutes, and then cooled to room temperature to obtain an emulsion. The resulting emulsion was adjusted to pH 5.0 using an aqueous solution of ammonium hydroxide (25% aqueous solution, also referred to as AW) to obtain an aqueous dispersion with a solid content concentration of 40%. For the particulate copolymer in the resulting aqueous dispersion, Tg, average particle size, and storage modulus were measured by the above-mentioned methods, and the heat shrinkability and peel strength were evaluated. The evaluation results are shown in Tables 1 to 6.

[0119] (Formation of coating film) A dispersion for forming a porous layer was prepared by uniformly dispersing 100 parts by mass (solid content concentration 50%) of aluminum oxide hydroxide particles (average particle diameter 1.0 μm) serving as an inorganic filler, 3.0 parts by mass of an aqueous dispersion (solid content concentration 40%) containing a synthesized particulate copolymer serving as a resin binder, and 0.5 parts by mass of an amine polyphosphate salt (dispersant solid content concentration 1%) serving as an ion dissociative inorganic dispersant. The prepared dispersion for forming a porous layer was applied to the surface of a polyethylene porous substrate that had been previously corona-treated, using a bar coater. Thereafter, the coating was dried at 60° C. for 1 minute to remove water, whereby a porous layer having a thickness of 2 μm was formed on the polyethylene porous substrate, to obtain a coating film having a total thickness of 17 μm. The evaluation results are shown in Tables 1 to 6 below. As the "polyphosphoric acid", tripolyphosphoric acid was used.

[0120] [Examples 2 to 21, Comparative Examples 1 to 10] The monomers and surfactants for forming the particulate copolymer were blended as shown in the following Tables 1 to 6. Other conditions: Emulsion polymerization was carried out in the same manner as in Example 1 to obtain an aqueous dispersion of the particulate copolymer. In addition, in Tables 1 to 6, TMPT is trimethylolpropane triacrylate, EDMA is ethylene glycol diacrylate, MA is methyl acrylate; EA is ethyl acrylate; CHMA is cyclohexyl methacrylate; NMAM is N-methylolacrylamide; DBS-Na is dodecylbenzenesulfonic acid; APS is ammonium persulfate, Each refers to: Moreover, in the same manner as in Example 1, a porous layer was prepared according to the above (Formation of the coating film). For the particulate copolymer in the obtained aqueous dispersion, Tg, average particle size, and storage modulus were measured by the above-mentioned methods, and the adhesion, heat shrinkage resistance, solution stability, slurry blending workability, water content of the separator, rate characteristics, and cycle characteristics were evaluated. The evaluation results are shown in Tables 1 to 6.

[0121] [Table 1]

[0122] [Table 2]

[0123] [Table 3]

[0124] [Table 4]

[0125] [Table 5]

[0126] [Table 6] [Industrial Applicability]

[0127] The nonaqueous secondary battery binder of the present invention has industrial applicability as a material for secondary battery separators.

Claims

1. A non-aqueous secondary battery binder comprising an aqueous medium and a particulate copolymer, The particulate copolymer contains vinyl monomer units, The vinyl monomer units include an acrylamide monomer unit (B1) and a methacrylamide monomer unit (B2), a content W1 (parts by mass) of the acrylamide monomer unit (B1) and a content W2 (parts by mass) of the methacrylamide monomer unit (B2) relative to 100 parts by mass of the total mass of the vinyl monomer units satisfy the following formula (1): The content W2 of the methacrylamide monomer unit (B2) is 2 parts by mass or more, The binder for a non-aqueous secondary battery is a binder for a functional layer included in a separator for a lithium ion secondary battery in the non-aqueous secondary battery. A binder for non-aqueous secondary batteries. 0<W1 / W2<1...(1)

2. The particulate copolymer has a glass transition temperature of 10° C. or less. The binder for a non-aqueous secondary battery according to claim 1 .

3. The particulate copolymer contains a vinyl monomer unit and a monomer unit derived from a reactive surfactant having a functional group copolymerizable with a vinyl group. The binder for a non-aqueous secondary battery according to claim 1 .

4. The vinyl monomer unit includes a crosslinkable monomer unit containing two or more vinyl groups, The content of the crosslinkable monomer unit containing two or more vinyl groups is 0.1 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the particulate copolymer. The binder for a non-aqueous secondary battery according to claim 1 .

5. The content W2 of the methacrylamide monomer unit (B2) relative to 100 parts by mass of the total mass of the vinyl monomer units is 2 parts by mass or more and less than 20 parts by mass; The binder for a non-aqueous secondary battery according to claim 1 .

6. The particulate copolymer has a volume average particle diameter Dv and a number average particle diameter Dn, the ratio Dv / Dn being: 1 or more and 1.5 or less, The binder for a non-aqueous secondary battery according to claim 1 .

7. The particulate copolymer is Storage modulus at 30°C is 7 x 10 7 Pa or more 5×10 8 Pa or less, Storage modulus at 130°C is 2 x 10 6 Pa or more, The binder for a non-aqueous secondary battery according to claim 1 .

8. The vinyl monomer units further include an epoxy group-containing vinyl monomer unit. The binder for a non-aqueous secondary battery according to claim 1 .

9. The binder for a non-aqueous secondary battery is a binder for a porous layer in a non-aqueous secondary battery; The binder for a non-aqueous secondary battery according to claim 1 .

10. Water, An inorganic filler; The binder for a non-aqueous secondary battery according to any one of claims 1 to 9, , including, Slurry for porous layers of lithium-ion secondary batteries.

11. The slurry for a lithium ion secondary battery porous layer according to claim 10 is included. Lithium-ion secondary battery porous layer.

12. The lithium ion secondary battery comprises the porous layer according to claim 11. Separator for lithium-ion secondary batteries.

13. A lithium ion secondary battery comprising the separator for lithium ion secondary batteries according to claim 12.

Citation Information

Patent Citations

  • Dividing device

    JP1982008872A

  • Oxygen permeable composite film for battery and its manufacture

    JP1992014755A

  • Motor torque controller for electric vehicle

    JP1999008908A

  • Electrochemical cell acrylic water dispersion and aqueous paste and manufacturing method of electrode and battery consisting of the same

    JP2012151108A

  • Binder for nonaqueous secondary batteries, resin composition for nonaqueous secondary batteries, nonaqueous secondary battery separator, nonaqueous secondary battery electrode, and nonaqueous secondary battery

    JP2015088484A